2016
DOI: 10.1002/ccd.26783
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular and hybrid intraoperative stent placement for baffle obstruction in transposition of the great arteries after atrial switch

Abstract: This study is the largest reported experience of intravascular and intra-operative hybrid stent placement for patients with TGA after atrial switch. Transcatheter and minimally invasive hybrid intraoperative surgical stent placement are an effective strategy for relief of systemic and pulmonary venous baffle obstruction. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Percutaneous intervention is often feasible for systemic venous baffle obstruction and successful in improving symptoms and/or facilitating nonobstructing access for transvenous pacemaker or defibrillator leads. 177,178 Leaks in the interatrial baffles are more common than clinically suspected, detectable in up to 65% of patients using echocardiography with saline contrast. 179 Transesophageal echocardiography is helpful to identify the size and location of the interatrial communication.…”
Section: Recommendations For Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous intervention is often feasible for systemic venous baffle obstruction and successful in improving symptoms and/or facilitating nonobstructing access for transvenous pacemaker or defibrillator leads. 177,178 Leaks in the interatrial baffles are more common than clinically suspected, detectable in up to 65% of patients using echocardiography with saline contrast. 179 Transesophageal echocardiography is helpful to identify the size and location of the interatrial communication.…”
Section: Recommendations For Interventionmentioning
confidence: 99%
“…When HF, protein-losing enteropathy, or Fontan circulation failure are refractory to pharmacologic management and interventions, early referral for heart transplantation assessment should be undertaken. [171][172][173][174][175][176][177][178][179][180][181][182][183][184] This should be to a centre with expertise in heart transplantation in the Fontan population. Decision-making around the appropriate timing for transplantation and consideration of multiorgan transplantation is challenging.…”
Section: Recommendations For Interventionmentioning
confidence: 99%
“…While historically baffle complications were managed surgically, perioperative mortality for surgical baffle revision after the atrial switch procedure has been reported in up to 36% of cases [ 16 ]. Percutaneous interventions are the preferred option in these adult patients, given the usually high perioperative risk due to previous thoracotomies, extensive adhesions, and concomitant heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In a report of their single‐center retrospective study of 20 patients treated between 1994 and 2016, Poterucha et al describe intravascular and hybrid stent placement for systemic and pulmonary venous baffle obstruction in patients who have undergone atrial switch repair for d‐transposition of the great arteries (d‐TGA). The study looked to assess the procedural success rate, clinical outcomes, and complications of this complex cohort.…”
mentioning
confidence: 99%